Perancangan Dan Pembuatan Alat Pengering Cengkeh Berbahan Bakar Biomassa - Latif, Lita Asyriati; Tjiroso, Bambang (Department of Electrical Engineering, University of Patria Artha, 2020)
Cloves are one of the leading agricultural commodities in North Maluku. The main product of the clove plant is clove flower. The clove flowers used in the production of kretek are dried cloves. Drying clove flowers can be done in two ways, first traditionally by drying them in the hot sun directly, and second by using an artificial dryer. Drying by drying directly in the sun or traditionally has several weaknesses, namely dependence on the weather, causing damage to clove flowers due to too long drying and the need for a large area for drying. The purpose of this research is to design and manufacture a clove dryer equipped with a biomass furnace as a heat source. The research method that will be carried out in this research is experimental research, by designing and building a clove dryer equipped with a biomass furnace as a heat source. The result is a clove dryer with dimensions of 120 cm long, 80 cm wide and 80 cm high. clove dryer equipped with 3 shelves with a distance of 20 cm between the racks. The clove dryer test results show that the time required to dry 18 kg of wet cloves is 13 hours with temperatures in the drying room 49 â„ƒ to 55 â„ƒ.